Barium titanate-based ceramic material, preparation method thereof and capacitor
By introducing specific elements and controlling element content into barium titanate-based ceramic materials, and combining high-temperature solid phase method to synthesize ceramic materials, the problem of unreliable operation of existing capacitors in high-temperature environments is solved, and the problem of unreliable operation between -55 degrees and 200 degrees is achieved Stable performance and low dielectric loss within the interval, suitable for capacitors in high temperature applications.
Patent Information
- Application Number
- CN202411547390.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
Existing capacitors cannot operate reliably in high temperature environments, requiring an external cooling system, which increases the volume, weight and cost of the system, and is difficult to meet the high-temperature application needs of more than 200 degrees.
Using barium titanate-based ceramic material, the chemical formula is (1-x)(Ba1-yCay-zSrz)TiO3-xBi(Mg0.5Zr0.5)O3, the elements are controlled by introducing Ca, Bi, Mg, Zr and Sr elements. The content was to achieve X9R characteristics, and ceramic materials were synthesized by high-temperature solid phase method.
It realizes that the capacitance value change is less than 15% within the range of -55 degrees to 200 degrees, achieves the X9R characteristic, and controls the dielectric loss below 0.9%, which is suitable for capacitors in high-temperature application scenarios.
Smart Images

Figure BDA0005114147790000061
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic materials, and specifically relates to a barium titanate-based ceramic material and a preparation method thereof, and particularly relates to a capacitor. Background Art
[0002] Capacitors are important electronic components in electronic power systems, playing the role of smoothing, energy storage, filtering, etc. in circuits. With the development of technology, more and more applications require the use of high-temperature capacitors, such as inverters in electric vehicles and photovoltaic power stations, electronic systems in the aerospace field, etc., which undoubtedly poses a challenge to existing capacitors.
[0003] The existing capacitors mainly include electrolytic capacitors, film capacitors and ceramic capacitors. The capacity of electrolytic capacitors decays quickly in high temperature environments, and there is a risk of leakage. Film capacitors soften or even melt at high temperatures because their dielectric layer is made of polymer materials; although ceramic capacitors can withstand higher temperatures without changing their macroscopic structure, the conductivity of ceramics will increase at the microscopic level and they will not be able to maintain insulation.
[0004] In high temperature environments, the three existing capacitors cannot work reliably and require an external cooling system, which increases the size, weight and cost of the entire system.
[0005] At present, the maximum operating temperature of aluminum electrolytic capacitors is 85-105 degrees, the maximum operating temperature of polypropylene (PP) film capacitors is 105 degrees; the maximum operating temperature of polyethylene naphthalate (PEN), polyethylene terephthalate (PET), and polyphenylene sulfide (PPS) film capacitors is 125 degrees. In ceramic capacitors, the maximum operating temperature that can achieve X7R characteristics is 125 degrees (X7R, where X represents the minimum operating temperature of -55 degrees, 7 represents the maximum operating temperature of 125 degrees, and R represents the capacitance value change within this temperature range is less than 15%), and the maximum operating temperature that can achieve X8R characteristics can reach 150 degrees. Researchers have proposed the next generation of high-temperature capacitors with X9R characteristics, and the maximum operating temperature can reach 200 degrees. However, there is currently little research on X9R high-temperature capacitors, so providing a capacitor ceramic material with a maximum operating temperature of more than 200 degrees that meets the X9R characteristics will have broad application prospects. Summary of the invention
[0006] The present invention is based on the inventor's discovery and understanding of the following facts and problems: the three existing capacitors cannot be reliably used in high temperature environments due to their insufficient stable operating temperature range. Therefore, it is necessary to study and improve the materials of the capacitors.
[0007] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, an embodiment of the present invention proposes a barium titanate-based ceramic material, which has a wider temperature range, a capacitance value change of less than 15% in the range of -55 degrees to 200 degrees, can achieve X9R characteristics, and a simple preparation method, which is easy for industrial application.
[0008] The barium titanate-based ceramic material of the embodiment of the present invention has the chemical formula: (1-x)(Ba 1-y Ca y-z Sr z )TiO 3 -xBi(Mg 0.5 Zr 0.5 ) 3 , where 0.20≤x≤0.25, 0.2≤y≤0.25, and 0≤z≤0.05.
[0009] Advantages and technical effects brought by the barium titanate-based ceramic material of the embodiment of the present invention: 1. In the ceramic material of the embodiment of the present invention, barium titanate is used as the matrix material. By introducing the Ca element, the dielectric loss can be reduced and the dielectric constant can be improved. At the same time, Bi, Mg, and Zr elements are introduced. Bi can improve the dielectric constant, Mg can improve the breakdown strength and insulation resistance, and Zr can improve the breakdown strength, insulation resistance and temperature stability of the dielectric constant; 2. In the embodiment of the present invention, the Sr element can also be introduced to further improve the dielectric constant; 3. In the embodiment of the present invention, by strictly controlling the content of each element, a ceramic material that can meet the X9R characteristic requirements is obtained, and the dielectric loss can be controlled below 0.9%. It is suitable for preparing capacitors in high-temperature application scenarios and has broad application prospects.
[0010] In some embodiments, 0.23≤x≤0.25.
[0011] In some embodiments, <z≤0.05。
[0012] The embodiment of the present invention also provides a method for preparing a barium titanate-based ceramic material, comprising the following steps:
[0013] (1) BaCO 3 、CaCO 3 、SrCO 3 、Bi 2 O 3 、TiO 2 、MgO、ZrO 2 Mix according to the designed ratio, perform the first ball milling process, and dry to obtain powder:
[0014] (2) pre-calcining the powder obtained in step (1) to obtain pre-calcined powder;
[0015] (3) subjecting the pre-sintered powder obtained in step (2) to a second ball milling process, and obtaining a ceramic powder after drying;
[0016] (4) pressing the ceramic powder obtained in step (3) into tablets, and subjecting the tablets to cold isostatic pressing to obtain a ceramic embryo;
[0017] (5) subjecting the ceramic body obtained in step (4) to a debinding treatment;
[0018] (6) The upper surface and the lower surface of the ceramic body obtained after the binder removal treatment in step (5) are respectively covered with the pre-fired powder obtained in step (2), and the barium titanate-based ceramic material is obtained after sintering.
[0019] The advantages and technical effects brought by the preparation method of barium titanate-based ceramic material in the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, a high-temperature solid-phase method is used to synthesize ceramic materials, and the process operation is simple and easy to apply; 2. In the embodiment of the present invention, pre-fired powder is respectively covered on the upper and lower surfaces of the ceramic body after debinding treatment, which is beneficial to reduce the volatilization of elements in the ceramic body; 3. The ceramic material prepared by the method of the embodiment of the present invention has a capacitance value change of less than 15% in the range of -55 degrees to 200 degrees, and can achieve X9R characteristics.
[0020] In some embodiments, in step (1), the first ball milling treatment time is 6-12 hours.
[0021] In some embodiments, in step (2), the temperature of the pre-sintering treatment is 800-900° C., the time is 2-8 hours, and preferably, the heating rate is 3-10° C. / min.
[0022] In some embodiments, in step (3), the second ball milling treatment includes: ball milling the pre-burned powder for 20 to 24 hours, then adding a binder, and continuing the ball milling treatment for 1 to 3 hours. Preferably, the binder includes RHOPLEX HA-8, and the amount of the binder added is 0.1 to 0.5% of the mass of the pre-burned powder.
[0023] In some embodiments, in step (4), the tabletting pressure is 50-100 MPa, the cold isostatic pressing pressure is 200-300 MPa, and the cold isostatic pressing processing time is 1-10 minutes.
[0024] In some embodiments, in step (5), the debinding treatment includes heating the ceramic body to 500-700° C. and keeping the temperature for 1-4 hours. Preferably, the heating rate is 0.5-3° C. / min.
[0025] In some embodiments, in step (6), the sintering temperature is 1100-1350° C., the sintering time is 1-4 hours, and preferably, the heating rate is 3-7° C. / min.
[0026] The embodiment of the present invention also provides an application of a barium titanate-based ceramic material in an inverter in an electric vehicle or a photovoltaic power station, or an electronic system in the aerospace field. The barium titanate-based ceramic material of the embodiment of the present invention has X9R characteristics and can be used in applications with high temperature requirements.
[0027] The embodiment of the present invention further provides a capacitor, which is made of the barium titanate-based ceramic material of the embodiment of the present invention. The capacitor of the embodiment of the present invention, made of the ceramic material of the embodiment of the present invention, has all the advantages that the ceramic material of the embodiment of the present invention can bring, which will not be repeated here. DETAILED DESCRIPTION
[0028] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0029] The barium titanate-based ceramic material of the embodiment of the present invention has the chemical formula: (1-x)(Ba 1-y Ca y-z Sr z )TiO 3 -xBi(Mg 0.5 Zr 0.5 ) 3 , where 0.20≤x≤0.25, 0.2≤y≤0.25, and 0≤z≤0.05.
[0030] In the barium titanate-based ceramic material of the embodiment of the present invention, barium titanate is used as the matrix material. By introducing the Ca element, the dielectric loss can be reduced and the dielectric constant can be improved. At the same time, Bi, Mg, and Zr elements are introduced. Bi can improve the dielectric constant, Mg can improve the breakdown strength and insulation resistance, and Zr can improve the breakdown strength, insulation resistance, and temperature stability of the dielectric constant. In the embodiment of the present invention, the Sr element can also be introduced to further improve the dielectric constant. In the embodiment of the present invention, by strictly controlling the content of each element, a ceramic material that can meet the X9R characteristic requirements is obtained, and the dielectric loss can be controlled below 0.9%. It is suitable for preparing capacitors in high-temperature application scenarios and has broad application prospects.
[0031] In some embodiments, 0.20 ≤ x ≤ 0.25, such as 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, etc., and preferably 0.23 ≤ x ≤ 0.25. In the embodiments of the present invention, by using the optimized value of x, the performance of the ceramic material can be further improved, which is beneficial to increasing the maximum service temperature to above 235°C. If the value of x is too small, it will cause the dielectric peak to shift to a lower temperature and the conductivity to increase, resulting in a decrease in the maximum service temperature and an increase in dielectric loss. If the value of x is too large, it will cause the dielectric peak to shift to a higher temperature. Although the maximum service temperature can be significantly increased, the minimum service temperature also increases, making it impossible to be applied in a low-temperature scenario of -55°C.
[0032] In some embodiments, 0.20 ≤ y ≤ 0.25, such as 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, etc. In the embodiments of the present invention, by controlling the value of y, while the ceramic material satisfies the X9R characteristics, the dielectric loss can be further reduced. If the value of y is too large, impurity phases are likely to appear in the ceramic material, reducing the stability of the material. If the value of y is too small, it will cause the dielectric peak to shift to a lower temperature. Although the dielectric loss can be reduced, the maximum service temperature shows a decrease, making it impossible to meet the application scenario requirements above 200°C.
[0033] In some embodiments, 0 < z ≤ 0.05, such as 0.01, 0.02, 0.03, 0.04, 0.05, etc. In the embodiments of the present invention, the Sr element can be further introduced, and the Sr element partially replaces the Ca element, enabling the ceramic material to further reduce the dielectric loss and increase the dielectric constant while satisfying the X9R characteristics.
[0034] The embodiments of the present invention also provide a preparation method for a barium titanate-based ceramic material, including the following steps:
[0035] (1) Mix BaCO 3 , CaCO 3 , SrCO 3 , Bi 2 O 3 , TiO 2 , MgO, ZrO 2 according to the designed ratio, perform the first ball milling treatment, and dry to obtain a powder:
[0036] (2) Perform a pre-sintering treatment on the powder obtained in step (1) to obtain a pre-sintered powder;
[0037] (3) Perform a second ball milling treatment on the pre-sintered powder obtained in step (2), and dry to obtain a ceramic powder;
[0038] (4) Press the ceramic powder obtained in step (3) into a tablet, and obtain a ceramic blank after cold isostatic pressing;
[0039] (5) subjecting the ceramic body obtained in step (4) to a debinding treatment;
[0040] (6) The upper surface and the lower surface of the ceramic body obtained after the binder removal treatment in step (5) are respectively covered with the pre-fired powder obtained in step (2), and the barium titanate-based ceramic material is obtained after sintering.
[0041] In the preparation method of the barium titanate-based ceramic material in the embodiment of the present invention, a high-temperature solid-phase method is used to synthesize the ceramic material. The process operation is simple and easy to apply. In addition, pre-fired powder is respectively covered on the upper and lower surfaces of the ceramic body after debinding treatment, which is beneficial to reduce the volatilization of elements in the ceramic body. The ceramic material prepared by the method of the embodiment of the present invention has a capacitance value change of less than 15% in the range of -55 degrees to 200 degrees, and can achieve X9R characteristics.
[0042] In some embodiments, in step (1), the first ball milling treatment time is 6-12 hours.
[0043] In some embodiments, in step (2), the temperature of the pre-sintering treatment is 800-900° C., the time is 2-8 hours, and preferably, the heating rate is 3-10° C. / min.
[0044] In some embodiments, in step (3), the second ball milling process comprises: ball milling the pre-sintered powder for 20 to 24 hours, then adding a binder, and continuing the ball milling process for 1 to 3 hours. Preferably, the binder comprises RHOPLEX HA-8, and the amount of the binder added is 0.1 to 0.5% of the mass of the pre-sintered powder. In the embodiment of the present invention, the pre-sintered powder is subjected to a secondary ball milling process, which can further improve the subsequent sintering activity while reducing the particle size.
[0045] In some embodiments, in step (4), the tabletting pressure is 50-100 MPa, the cold isostatic pressing pressure is 200-300 MPa, and the cold isostatic pressing treatment time is 1-10 minutes. In the embodiment of the present invention, the ceramic powder is tableted and cold isostatically pressed to further improve the density of the ceramic body.
[0046] In some embodiments, in step (5), the debinding treatment includes heating the ceramic body to 500-700° C. and keeping the temperature for 1-4 hours. Preferably, the heating rate is 0.5-3° C. / min.
[0047] In some embodiments, in step (6), the sintering temperature is 1100-1350° C., the sintering time is 1-4 hours, and preferably, the heating rate is 3-7° C. / min.
[0048] The present invention is described in detail below with reference to embodiments.
[0049] Example 1
[0050] (1) BaCO 3 、CaCO 3 、Bi 2 O 3 、TiO 2 、MgO、ZrO 2 As raw materials, the ingredients are prepared according to the stoichiometric ratio of the chemical formula of barium titanate-based ceramic materials in Table 1 to obtain a raw material mixture, which is subjected to the first ball milling treatment for 10 hours and then dried to obtain a powder:
[0051] (2) heating the powder to 850° C. at a rate of 5° C. / min and calcining for 3 h to obtain pre-calcined powder;
[0052] (3) The pre-sintered powder was subjected to a second ball milling treatment, first ball milling for 21 hours, then a binder RHOPLEX HA-8 was added, ball milling was continued for 1.5 hours, and then dried to obtain a ceramic powder;
[0053] (4) After pressing the ceramic powder into a disc at 80 MPa, cold isostatic pressing is performed at 220 MPa for 5 minutes to increase the density of the ceramic body, thereby obtaining a ceramic body;
[0054] (5) heating the ceramic body to 600° C. at a rate of 1° C. / min, keeping the temperature for 2 h, performing a binder removal treatment, and then cooling the ceramic body to room temperature;
[0055] (6) The upper and lower surfaces of the debinding ceramic body are respectively covered with pre-fired powder of the same composition as that treated in steps (1) and (2) to reduce the volatilization of elements in the ceramic body, and then the temperature is increased to 1150° C. at 5° C. / min and sintered for 3 hours to obtain a ceramic material.
[0056] Embodiment 2-7
[0057] The method is the same as that of Example 1, except that the chemical formula of the prepared ceramic material is different, as shown in Table 1.
[0058] Example 8
[0059] The method is the same as that of Example 1, except that SrCO is added in step (1). 3 .
[0060] The chemical formula of the ceramic material prepared in Example 8 is shown in Table 1.
[0061] Comparative Example 1
[0062] The method is the same as that of Example 1, except that Bi is not added in step (1). 2 O3 , MgO and ZrO 2 .
[0063] Comparative Example 2
[0064] The method is the same as that of Example 1, except that no CaCO is added in step (1). 3 .
[0065] Comparative Examples 2-8
[0066] The method is the same as that of Example 1, except that the chemical formula of the prepared ceramic material is different, as shown in Table 1.
[0067] Comparative Example 9
[0068] The method is the same as that of Example 8, except that the CaCO added in step (1) 3 and SrCO 3 The amount is different.
[0069] The chemical formula of the ceramic material prepared in Comparative Example 9 is shown in Table 1.
[0070] The performance of the ceramic materials prepared in each embodiment and comparative example was tested, and the test results are shown in Table 1.
[0071] Test method: Grind the ceramic sheet samples prepared in each embodiment and comparative example, clean them ultrasonically in acetone and ethanol in turn, and dry them; print silver electrodes on both sides of the ceramic sheet with a screen printer, and bake them at 850°C for 20 minutes to strengthen the adhesion between silver and ceramic. Clamp the ceramic sheet with electrodes on a variable temperature test bench, and connect the electrodes at both ends to an impedance analyzer. Control the temperature rise of the test bench through a computer program, record the dielectric constant and dielectric loss of the ceramic at different temperatures, and calculate the temperature range when the dielectric constant change rate of different ceramics is 15%.
[0072] Table 1
[0073]
[0074] Note: 1. The dielectric constant and dielectric loss in the table are the dielectric constant and dielectric loss at room temperature (25°C);
[0075] 2. The lower limit of temperature refers to the lowest temperature when the ceramic dielectric constant changes by 15%;
[0076] 3. The upper temperature limit refers to the maximum temperature when the ceramic dielectric constant changes by 15%.
[0077] As can be seen from Table 1, in Examples 1-8 of the present application, Ca, Bi, Mg, Zr and Sr are introduced into the barium titanate substrate to prepare a barium titanate substrate having the chemical formula (1-x)(Ba 1-y Ca y-z Srz )TiO 3 -xBi(Mg 0.5 Zr 0.5 ) 3 The ceramic material of Examples 1-8 of the present application has the characteristics of X9R, and the dielectric loss can be controlled below 0.9%, with excellent performance, and can be used in capacitors for high temperature applications.
[0078] In Comparative Example 1, Bi, Mg and Zr were not introduced. Since the material has strong ferroelectricity, the dielectric properties change dramatically during the ferroelectric phase transition, and the maximum operating temperature is only 58°C.
[0079] In Comparative Example 2, the Ca element is not introduced. Since the material still retains some ferroelectricity, the dielectric peak is in the high temperature region and is relatively sharp. The maximum operating temperature is only 168°C.
[0080] In Comparative Example 3, the chemical formula (1-x) (Ba 1-y Ca y-z Sr z )TiO 3 -xBi(Mg 0.5 Zr 0.5 ) 3 The x value is relatively small, at 0.15. Although the dielectric loss is small, the material still retains some ferroelectricity, resulting in a sharp dielectric peak and a maximum operating temperature of only 131°C.
[0081] In Comparative Examples 4 and 5, the chemical formula (1-x) (Ba 1-y Ca y-z Sr z )TiO 3 -xBi(Mg 0.5 Zr 0.5 ) 3 The x values are 0.1 and 0.05, respectively. Compared with Example 1, not only the maximum operating temperature is greatly reduced to 111° C. and 120° C., but also the dielectric loss is increased to 3.54% and 4.94%, respectively.
[0082] In Comparative Example 6, the chemical formula (1-x) (Ba 1-y Ca y-z Sr z )TiO 3 -xBi(Mg 0.5 Zr 0.5 )3 When x increases to 0.30, although the maximum operating temperature reaches 337°C, the dielectric peak shifts to the high temperature region, resulting in a drastic change in the dielectric constant in the low temperature region, causing the minimum operating temperature to rise to -31°C, and the dielectric loss increases to 2.02%, which cannot meet the X9R requirement.
[0083] In Comparative Example 7, the chemical formula (1-x) (Ba 1-y Ca y-z Sr z )TiO 3 -xBi(Mg 0.5 Zr 0.5 ) 3 When y is reduced to 0.15, the dielectric peak moves to the low temperature region, resulting in a drastic change in the dielectric constant in the high temperature region, making it impossible for the maximum operating temperature to meet the requirement of 200°C.
[0084] In Comparative Example 8, the chemical formula (1-x) (Ba 1-y Ca y-z Sr z )TiO 3 -xBi(Mg 0.5 Zr 0.5 ) 3 When y increases to 0.3, the Ca content increases. Although the dielectric constant increases at room temperature, the dielectric peak shifts to the high temperature zone, and the dielectric constant changes dramatically in the low temperature zone, causing the minimum operating temperature to increase to -41°C, which cannot meet the X9R characteristic requirements.
[0085] In Comparative Example 9, the chemical formula (1-x) (Ba 1-y Ca y-z Sr z )TiO 3 -xBi(Mg 0.5 Zr 0.5 ) 3 When z increases to 0.1, the dielectric constant changes dramatically due to the appearance of the second phase, so that the maximum operating temperature can only reach 186℃, which cannot meet the requirement of 200℃.
[0086] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0087] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A barium titanate-based ceramic material, characterized in that: The chemical formula of the barium titanate-based ceramic material is: (1-x)(Ba 1-y Ca y-z Sr z )TiO3-xBi(Mg 0.5 Zr 0.5 )O3, where 0.20≤x≤0.25, 0.2≤y≤0.25, and 0≤z≤0.
05.
2. The barium titanate-based ceramic material according to claim 1, characterized in that: 0.23≤x≤0.25。 3. The barium titanate-based ceramic material according to claim 1, characterized in that: 0<z≤0.05。 4. A method for preparing the barium titanate-based ceramic material according to any one of claims 1 to 3, characterized in that: The steps include: (1) BaCO3, CaCO3, SrCO3, Bi2O3, TiO2, MgO and ZrO2 are mixed according to the designed ratio and subjected to the first ball milling treatment, and then dried to obtain a powder: (2) pre-calcining the powder obtained in step (1) to obtain pre-calcined powder; (3) subjecting the pre-sintered powder obtained in step (2) to a second ball milling process, and obtaining a ceramic powder after drying; (4) pressing the ceramic powder obtained in step (3) into tablets, and subjecting the tablets to cold isostatic pressing to obtain a ceramic embryo; (5) subjecting the ceramic body obtained in step (4) to a binder removal treatment; (6) The upper surface and the lower surface of the ceramic body obtained after the binder removal treatment in step (5) are respectively covered with the pre-fired powder obtained in step (2), and the barium titanate-based ceramic material is obtained after sintering.
5. The method for preparing a barium titanate-based ceramic material according to claim 4, characterized in that: In the step (1), the first ball milling treatment time is 6-12 hours; And / or, in the step (2), the temperature of the pre-sintering treatment is 800-900° C., the time is 2-8 hours, and preferably, the heating rate is 3-10° C. / min.
6. The method for preparing a barium titanate-based ceramic material according to claim 4, characterized in that: In the step (3), the second ball milling treatment comprises: ball milling the pre-sintered powder for 20 to 24 hours, then adding a binder, and continuing the ball milling treatment for 1 to 3 hours. Preferably, the binder comprises RHOPLEX HA-8, and the amount of the binder added is 0.1 to 0.5% of the mass of the pre-sintered powder.
7. The method for preparing a barium titanate-based ceramic material according to claim 4, characterized in that: In the step (4), the tabletting pressure is 50 to 100 MPa, the cold isostatic pressing pressure is 200 to 300 MPa, and the cold isostatic pressing processing time is 1 to 10 minutes.
8. The method for preparing a barium titanate-based ceramic material according to claim 4, characterized in that: In the step (5), the debinding treatment includes heating the ceramic body to 500-700° C. and keeping the temperature for 1-4 hours. Preferably, the heating rate is 0.5-3° C. / min. And / or, in the step (6), the sintering temperature is 1100-1350° C., the sintering time is 1-4 hours, and preferably, the heating rate is 3-7° C. / min.
9. Application of the barium titanate-based ceramic material according to any one of claims 1 to 3 or the barium titanate-based ceramic material prepared by the preparation method according to any one of claims 4 to 8 in inverters in electric vehicles or photovoltaic power stations, and electronic systems in the aerospace field.
10. A capacitor, characterized in that: The invention is made of the barium titanate-based ceramic material described in any one of claims 1 to 3 or the barium titanate-based ceramic material prepared by the preparation method described in any one of claims 4 to 8.
Citation Information
Patent Citations
Low-loss, high-temperature and lead-free capacitor material and preparation method thereof
CN105294097A
High-energy-storage barium titanate dielectric material and preparation method thereof
CN109133915A
Dielectric ceramic and manufacturing method therefor and laminated ceramic capacitor
US20100328844A1